Nouvelles données paléoenvironnementales dans le Sud de la France vers 30000 ans 14C BP : le cas de la grotte Marie (Hérault) - Crochet, Jean-Yves; Gence, Jean; Boulbes, Nicolas; Boutié, Paul; Cretin, Catherine; Crégut-Bonnoure, Évelyne; Duzer, Danièle; Jolly, Dominique; Laudet, Frédéric; Lefévre, David; Mourer-Chauviré, Cécile; Rousselières, France; et al. (Comptes Rendus Palevol, 2007)
The Marie cave, discovered to the north of Montpellier, Herault (France), has yielded a fauna of 28 vertebrates, out of which 23 are small ´ to large mammals, notably Mammuthus primigenius. The few discovered artefacts have been attributed to the Upper Palaeolithic, which is in agreement with the two radiocarbon dates (31450 14 C yr BP for the low level, and 28680 14 C yr BP near the cave’s entrance). The palynological study shows the existence (i) of a wooded steppe on the plateau, and (ii) of a riverine forest with alders in the valleys, associated with Mediterranean taxa. These data conﬁrm the presence in Languedoc of Mediterranean species around 30000 yr BP, which qualiﬁes the hypothesis of exclusively Spanish and Italian refuges during glacial periods
Keywords: France; Marie cave; Palaeoenvironment; palynology; Upper Palaeolithic; Vertebrates; Wurm

Palynology of the northwestern Mediterranean shelf (Gulf of Lions): First vegetational record for the last climatic cycle - Beaudouin, Célia; Suc, Jean-Pierre; Acherki, Nabila; Courtois, Laurent; Rabineau, Marina; Aloïsi, Jean-Claude; Sierro, Fransisco Javier; Oberlin, Christine (Marine and Petroleum Geology, 2005)
Palynology has been performed for the ﬁrst time on Late Quaternary sediments of the Gulf of Lions. The aim is both to tighten the chronology of seismic proﬁles in the region, and to elucidate the vegetation of southern France during the Last Climatic Cycle. Four cores, taken on the shelf, mostly record Marine Isotope Stages (MIS) 1 and 2 and part of MIS 3 and MIS 5. The latter sediments might have been preserved in a paleodepression on the emergent shelf between the Rhoˆne and the He´rault rivers. It would explain their preservation against transgression and regression erosions of more recent stages. This study also provides a synthesis of palynological continental data collected during the last 40 years in southern Europe. Preliminary comparisons made between the latter and new marine data demonstrate that refugia of Picea and Abies existed in southern France during MIS 3 and MIS 2. The dynamics of Artemisia, deciduous Quercus and Corylus, Abies and ﬁnally Fagus is also reconstructed for the last deglaciation. First results obtained in the Gulf of Lions conﬁrm and complete that synthesis.
Keywords: late quaternary; nw mediterranean sea; palynology

Vegetation dynamics in north-western Mediterranean regions: Instability of the Mediterranean bioclimate - De Beaulieu, J.-L.; Miras, Y.; Andrieu-Ponel, V.; Guiter, F. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract Pollen and plant macrofossil records from a selection of sites in Spain, France and Italy are used to explore the origin and the development of the Mediterranean vegetation. The role of evergreen and summergreen taxa is discussed. The expansion of sclerophyllous trees during the Pleistocene interglacials is well correlated with the orbital forcing. During the Holocene, the large number of data illustrates latitudinal and longitudinal differences in vegetation dynamics. Multidisciplinary studies identify short terms climatic fluctuations. The debate is still open between those who attribute an increase of sclerophyllous forests during the late Holocene to a trend toward aridity and those who consider this dynamic as human-induced.
doi: 10.1080/11263500500197858doi: 10.1080/11263500500197858The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: human impact; Mediterranean ecosystems; palaeoclimates; palynology; review